Use of telemedicine for rheumatology practice in Queensland, Australia: experiences before and during the COVID‐19 pandemic. Issue 10 (27th August 2022) - Jhaveri, Divita; Emeto, Theophilus I.; Alele, Faith O.; Strom, Aleisha; Benham, Helen
Abstract: Background: In Australia there is a shortage of rheumatologists potentially translating to poorer outcomes. A possible solution in this setting is telemedicine (TM). Aims: To examine the utilisation and provider perceptions of TM in rheumatology in Queensland and explore the challenges faced when using TM before and during COVID‐19. Methods: A sequential mixed‐methods study design was used. Rheumatologists completed a questionnaire on demographics, clinical practice, TM uptake, models of care and clinician perceptions of TM. The qualitative phase utilised purposeful sampling of active users of TM through in‐depth semi‐structured interviews. Results: Thirty rheumatologists participated, with 76.7% identifying as active TM users. Use of TM was limited prior to COVID‐19 with 80.9% examining less than five patients per week. Patient populations served by TM included capital city (53.3%), regional (63.3%) and rural/remote (23.3%). Most rheumatologists prescribed conventional or biological disease modifying agents (90% and 55%) through TM consultations. Barriers to TM use included low confidence in joint assessments, limited distribution of technology, access to administrative and peripheral clinical staff and lack of financial incentives. During the COVID‐19 pandemic, a significant expansion of TM via telephone calls occurred and rheumatologists reported low confidence and satisfaction with this model. Conclusions: Familiarity with TM exists in this rheumatologist cohort; however, its use in routine practice is limited due to multiple barriers. The COVID‐19 pandemic highlighted low confidence in telephone calls as a form of TM underlining the need for appropriate TM models of care for rheumatology practice.